First-in-class thyrotropin-releasing hormone (TRH)-based compound binds to a pharmacologically distinct TRH receptor subtype in human brain and is effective in neurodegenerative models. (February 2015) - Kelly, Julie A.; Boyle, Noreen T.; Cole, Natalie; Slator, Gillian R.; Colivicchi, M. Alessandra; Stefanini, Chiara; Gobbo, Oliviero L.; Scalabrino, Gaia A.; Ryan, Sinead M.; Elamin, Marwa; Walsh, Cathal; Vajda, Alice; et al.
Abstract: JAK4D, a first-in-class thyrotropin-releasing hormone (TRH)-based compound, is a prospective therapeutic candidate offering a multifaceted approach to treating neurodegeneration and other CNS conditions. The purpose of these studies was to determine the ability of JAK4D to bind to TRH receptors in human brain and to evaluate its neuropharmacological effects in neurodegenerative animal models. Additionally, JAK4D brain permeation was examined in mouse, and initial toxicology was assessed in vivo and in vitro . We report that JAK4D bound selectively with nanomolar affinity to native TRH receptors in human hippocampal tissue and showed for the first time that these receptors are pharmacologically distinct from TRH receptors in human pituitary, thus revealing a new TRH receptor subtype which represents a promising neurotherapeutic target in human brain. Systemic administration of JAK4D elicited statistically significant and clinically-relevant neuroprotective effects in three established neurodegenerative animal models: JAK4D reduced cognitive deficits when administered post-insult in a kainate (KA)-induced rat model of neurodegeneration; it protected against free radical release and neuronal damage evoked by intrastriatal microdialysis of KA in rat; and it reduced motor decline, weight loss, and lumbar spinal cord neuronal loss in G93A-SOD1 transgenic Amyotrophic Lateral Sclerosis mice. Ability to cross the blood–brain barrier and a clean initial toxicology profile were also shown. In light of these findings, JAK4D is an important tool for investigating the hitherto-unidentified central TRH receptor subtype reported herein and an attractive therapeutic candidate for neurodegenerative disorders. Highlights: First-in-class TRH-based compound JAK4D detects new receptor subtype in human brain. JAK4D elicits statistically significant effects in neurodegenerative animal models. JAK4D crosses the blood–brain barrier and has a clean initial toxicology profile. JAK4D is a tool to study central pharmacologically-distinct TRH receptor subtype. JAK4D is an attractive therapeutic candidate for neurodegenerative diseases.